2021
DOI: 10.22541/au.163344873.38613513/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide footprints in the carob tree (Ceratonia siliqua) unveil a new domestication pattern of fruit trees in the Mediterranean

Abstract: Intense research efforts on phylogeography over the last two decades uncovered major biogeographical trends and renewed our understandings of plant domestication in the Mediterranean. We aim to investigate the evolutionary history and the origin of domestication of the carob tree that has been cultivated for millennia for food and fodder. We used >1000 microsatellite genotypes to identify carob evolutionary units (CEUs) based on genetic diversity structure and geography. We investigated genome-wide diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Hence, the significant relationship between trait variability and geographic distance (Additional file 5: Appendix S3) reflects the effects of contrasting environmental conditions found among carob populations on seed trait variability. Therefore, the population genetic structure of Moroccan carob trees highlights clear discrimination between populations from the South and those from the North region (Baumel et al 2021), which could also explain the observed pattern of seed variation and differentiation. Baumel et al (2021) identified four main regions as the ancestral area of the carob evolutionary history, in which South Morocco and North Morocco with the Iberian Peninsula are two major areas.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Hence, the significant relationship between trait variability and geographic distance (Additional file 5: Appendix S3) reflects the effects of contrasting environmental conditions found among carob populations on seed trait variability. Therefore, the population genetic structure of Moroccan carob trees highlights clear discrimination between populations from the South and those from the North region (Baumel et al 2021), which could also explain the observed pattern of seed variation and differentiation. Baumel et al (2021) identified four main regions as the ancestral area of the carob evolutionary history, in which South Morocco and North Morocco with the Iberian Peninsula are two major areas.…”
Section: Discussionmentioning
confidence: 86%
“…However, recent phylogeographic evidence suggested a strong west-east genetic structuring and the presence of multiple domestication centers from native populations all over the Mediterranean basin. Consequently, four main genetic groups of C. siliqua are identified and correspond to South Morocco, the Iberian Peninsula, the Central Mediterranean, and the Eastern Mediterranean (Baumel et al 2021). In addition, the increasing commercial value of carob has triggered more attention to this multipurpose tree.…”
Section: Introductionmentioning
confidence: 99%
“…Dussex et al, 2016; Fabritzek & Kadereit, 2018; Wares et al, 2021; Zhao et al, 2018), as well as dispersal and secondary contact among populations (e.g. Baumel et al, 2022; Feulner & Seehausen, 2019; McCulloch et al, 2019; Vaux, Bohn, et al, 2021), for which there are specialised programs (Piry et al, 2004; Wringe et al, 2017). Robust filtering can be required to accurately estimate admixture though, particularly for genetic linkage and batch effects from combining GBS runs (Lambert et al, 2019), and genome coverage can influence results (Ottenburghs, 2021).…”
Section: Biogeographical Analysesmentioning
confidence: 99%
“…Bagley et al, 2020; Parvizi et al, 2020; Smith et al, 2020) and ecological (e.g. Baumel et al, 2022; McCulloch et al, 2019; Nicotra et al, 2016) processes that shape spatial biodiversity. GBS data frequently provide a greater degree of insight compared to traditional genetic markers using mitochondrial DNA or nuclear DNA microsatellites (Figure 1; see also examples in Parvizi, Fraser, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that carob tree is diploid, even though some cases of triploidy and tetraploidy have been found (Bureš et al 2004). Lately, based on genotypes from 17 microsatellite loci (including SSRs and SNPs) and geographical coordinates, 1,019 carob trees were grouped into seven carob evolutionary units (CEUs), with an interesting group being the E2, which involves the carob trees from Lebanon and Crete (Greece) (Figure 1) (Baumel et al 2022). It appears that there is a high frequency of carob trees in the landscape of Lebanon and Crete.…”
Section: Introductionmentioning
confidence: 99%